Critical assessment of chitotriosidase analysis in the rational laboratory diagnosis of children with Gaucher disease and Niemann-Pick disease type A/B and C - Ries, Markus; Schaefer, Ellen; Lührs, Till; Mani, Latha; Kuhn, Jana; Vanier, Marie T.; Krummenauer, Frank; Gal, Andreas; Beck, Michael; Mengel, Eugen (Journal of inherited metabolic disease, 2006)
Laboratory diagnosis of lysosomal storage disorders, especially sphingomyelinase deficiency (Niemann-Pick disease type A/B) and Niemann-Pick disease type C (NPC) can be challenging. We therefore aimed to analyse the feasibility of first-step screening with specific chitotriosidase cut-off values in children ≤ 10 years of age with visceral organomegaly (hepatomegaly, splenomegaly, or hepatosplenomegaly) in whom a storage disorder was suspected. We conducted a retrospective, cross-sectional, referral, single-centre study to assess diagnostic test properties in 106 individuals. Median chitotriosidase activity was 12 655 nmol/h per ml (interquartile range 4693-20982) in Gaucher disease (GD); 780 (465-1298) in SMD (sphingomyelinase deficiency); 925 (319-1215) in NPC and 50 (29-54) in patients with miscellaneous diseases. To restrict the differential diagnosis to GD, SMD or NPC, chitotriosidase activity above 200 nmol/h per ml had a sensitivity of 96%, specificity of 100%, positive predictive value (PPV) of 100%, and negative predictive value (NPV) of 95%. For GD alone, chitotriosidase activity above 4000 nmol/h per ml had a sensitivity of 77%, specificity of 100%, PPV of 100% and NPV of 92%. Of the 44 patients analysed, 4.5% were homozygous and 36.4% heterozygous for chitotriosidase gene duplication. Adjusting for the chitotriosidase genotype, chitotriosidase activities were higher in GD type III than in GD type I. We conclude that, in the above setting, the degree of elevation of chitotriosidase activity can be applied to increase the likelihood of GD, SMD, or NPC and guide the choice of the appropriate confirmatory assay.
Gesehen am 15.05.2019